Recent financial crises : analysis, challenges and implications - Klein, Lawrence R.; Shabbir, T. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
Financial crises are recurring phenomena that can cause significant economic and societal loss. This book analyzes why and how financial crises occur, the extent of their impact, and what can be done to prevent their recurrence or reduce the damage they cause. It offers insights on lessons to be learned from outbreaks in East Asia and elsewhere.
Includes bibliographical references and index.
oif 02/09/15, ijb 07/03/2019
Loan
Keywords: Financial crises; International economics